2004
DOI: 10.1080/00288233.2004.9513580
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of conjugated linoleic, trans‐vaccenic and long chain omega‐3 fatty acid content in raw and cooked lamb from two cross‐breeds

Abstract: Available literature mainly describes the fatty acid (FA) content of raw meat, with only limited data explaining the effect of different preparation and cooking temperatures on health-promoting FA such as conjugated linoleic acid (CLA), its metabolic precursor trans-vaccenic acid (TVA), and long chain omega-3 FA (LC omega-3 FA). We collected m. longissimus thoracis (LT) from rib chops of Poll Dorset × East Friesian (EF) and Poll Dorset × Romney (R) lambs raised together. The FA composition of raw LT was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The concentrations of both CLA and TVA in the LT from the lambs in this trial were lower than the concentrations of 1.9 g CLA and 4.7 g TVA 100 g-1 TFA found in lambs that had grown for 17 weeks on their mothers to a carcass weight of 18.5 kg before being slaughtered (Knight et al 2004). Those ewes grazed only grass and the lambs grew at 300 g day -1 , which could only have been achieved with high milk intakes by the lambs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The concentrations of both CLA and TVA in the LT from the lambs in this trial were lower than the concentrations of 1.9 g CLA and 4.7 g TVA 100 g-1 TFA found in lambs that had grown for 17 weeks on their mothers to a carcass weight of 18.5 kg before being slaughtered (Knight et al 2004). Those ewes grazed only grass and the lambs grew at 300 g day -1 , which could only have been achieved with high milk intakes by the lambs.…”
Section: Discussionmentioning
confidence: 83%
“…Dietary TVA has been shown to be a precursor for CLA in mice (Santora et al 2000) and humans (Salminen et al 1998). This suggests TVA in ruminant meat could be considered an additional dietary precursor of CLA in humans, especially since the concentrations of TVA in beef and lamb are up to five-fold higher than the concentrations of CLA (Knight et al 2003(Knight et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…This water loss was higher compared to 27.1% by micro-waving or 36.5% by broiling lamb meat to a core temperature of 75 7C [16]. Cooking lamb meat under a fan grill to 82 7C increased the cooking loss also to 45% [17]. The cooking loss was not affected by sex, feeding or storage time.…”
Section: Resultsmentioning
confidence: 81%
“…Badiani et al [21] reported no effect of different cooking procedures (dry-heat and moist-heat) on PUFA percentages in lamb muscle lipids. In another work, the cooking (at 200 7C) of lean intact longissimus lamb muscles or trimmed muscles reduced the percentage but increased the concentration of PUFA [17]. Grilling of chicken breast to an internal temperature of 85-90 7C with sunflower oil increased the UFA/SFA and PUFA/SFA ratios in comparison to raw samples [23].…”
Section: Storage and Processing Effectsmentioning
confidence: 95%
See 1 more Smart Citation